2006
DOI: 10.1080/01443610500443402
|View full text |Cite
|
Sign up to set email alerts
|

Demand and utilisation of labour analgesia service by Nigerian women

Abstract: This study sought to determine the clinical correlates of the demand and utilisation of labour analgesia resources by Nigerian women in labour. All consenting women were interviewed on arrival at the Unit and while in labour. Biodata, options for relief of labour pain, request for analgesia, method of analgesia, VAS score and cervical score at time of request for analgesia were obtained. A total of 288 women in labour were studied. Of these, 108 (37.5%) patients were aware that the pain of labour can be reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…This is comparable to the level of awareness of labor analgesia reported by previous studies [7,11]. Various studies done in Nigeria on the level of awareness of labor analgesia reported 15-64% [4,5,10,16,18,19]. This is similar to what was reported from some other developing countries [11][12][13]15].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is comparable to the level of awareness of labor analgesia reported by previous studies [7,11]. Various studies done in Nigeria on the level of awareness of labor analgesia reported 15-64% [4,5,10,16,18,19]. This is similar to what was reported from some other developing countries [11][12][13]15].…”
Section: Discussionsupporting
confidence: 80%
“…Labor is seen as excruciatingly painful among most Nigerian women [1][2][3][4][5]. The pain of labor is not known to be beneficial to the process of labor; and it can be a source of extreme discomfort to the parturient [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers in Nigeria found that few of their respondents reported that labour analgesia was taught at prenatal classes. [6][7] The fact that 31.4% of this study respondents said they were not aware that non-pharmacological methods of pain control exist in the hospital of study may imply that they were not part of the routine antenatal care discussion in the study centre or respondents have not attended such sessions. Furthermore, the finding that respondents' knowledge peaked at parity of two but decreased at parity of three and above seems to suggest a decreasing interest of multi-parous women to learn these methods.…”
Section: Discussionmentioning
confidence: 99%
“…3 While 85% of surveyed women in a developing country indicated they would request labour analgesia if available, only 40% received any analgesia in practice. 4 The cost of staff and supplies associated with providing epidurals can be prohibitive, with morphine costing up to 10 times more in low-resource settings than in the developed world. 5,6 With limited resources for epidural analgesia, spinal analgesia may be a useful alternative for relief from labour pain.…”
Section: Introductionmentioning
confidence: 99%